Cofactor of BRCA1 as a modulator of hepatocellular carcinoma growth and migration - El Zeneini, Eman Mahmoud (AUC Knowledge Fountain, 2015)
Cofactor of BRCA1 (COBRA1) is one of the four subunits that make up the Negative Elongation Factor Complex (NELF) which is involved in the stalling of RNA polymerase II early during transcription elongation. As such, COBRA1 is able to regulate a substantial number of genes involved in a number of pathways, including cell cycle control, metabolism, cell proliferation and DNA repair. In the field of cancer, the role of COBRA1 is not yet fully understood. The aim of our study was to investigate the functional role of COBRA1 in the tumorigenesis of hepatocellular carcinoma (HCC). We investigated the gene expression pattern of COBRA1 in HCC tumors using the publicly available Oncomine Cancer Microarray Database. Results from three different microarray datasets reveal the frequent overexpression of COBRA1 in HCC tumors versus their normal counterparts. To elucidate the biological significance for this overexpression in HCC, RNA interference was used to silence the expression of COBRA1 in the well differentiated HCC cell line, HepG2. The silencing efficiency was confirmed by both reverse transcription-polymerase chain reaction (RT-PCR) and Western blot analysis. Interestingly, knockdown of COBRA1 resulted in a significant decrease in cell proliferation, accompanied by a concomitant decrease in the expression of the proliferation marker, Ki-67. A scratch wound healing assay revealed a significant decrease in the migratory potential of the HepG2 cell line in culture upon COBRA1 knockdown. In addition, silencing of COBRA1 was associated with a significant decrease in the expression of survivin, suggesting that survivin might be one of the mechanisms by which COBRA1 mediates its role in the tumorigenicity of HCC. Collectively, data findings presented here highlight an oncogenic role for COBRA1 in hepatocellular carcinoma. To the best of our knowledge, our study provides evidence for the first time to support a positive role for COBRA1 in the growth and migration of HCC.